Implementasi aplikasi TOEFL Test Pro berbasis android bagi Mahasiswa Universitas Hafshawaty Zainul Hasan - Sulistiana, Eva; Adianto, Arda; Nadzifah, Wardatun (Jurnal Dedikasi Masyarakat, 2024)
TOEFL test-takers with limited grammar (structure) proficiency tend to achieve lower scores. To enhance structure skills, continuous and intensive learning and practice are required. However, many test-takers experience difficulties and boredom when studying structure due to its perceived complexity and lack of engagement. Therefore, an interactive and effective learning medium is needed to facilitate easier and more enjoyable grammar acquisition. The TOEFL Test Pro (Android-Based Application) serves as a potential solution to improve the grammar proficiency of students at Universitas Hafshawaty Zainul Hasan. This community engagement program was implemented in three phases: preparation, execution, and evaluation. The program involved 47 first-year students from Universitas Hafshawaty and was conducted at the university’s premises in Pajarakan, Probolinggo. Evaluation results indicate that after the training, students demonstrated greater enthusiasm in learning and answering TOEFL questions, particularly in the structure or grammar section. The accessibility and interactive features of the TOEFL Test Pro application played a key role in increasing students' learning motivation. Additionally, the question explanation feature helped students identify and understand their mistakes, significantly improving their grammar comprehension. The daily reminder feature further encouraged students to consistently access the application and engage in intensive TOEFL practice, ultimately leading to a projected gradual improvement in their scores.